IDDF2018-ABS-0057 Biofeedback in patients with ileoanal pouch dysfunction: a specialist centre experience. (June 2018) - Segal, Jonathan; Chan, Heyson; Collins, Brigitte; Faiz, Omar; Clark, Susan; Hart, Ailsa
Abstract : Background: Restorative proctocolectomy is performed in patients with UC refractory to medical therapy, UC related neoplasia, and in some patients with familial adenomatous polyposis. Incontinence can occur in up to 12%–31% of patients with an ileoanal pouch. Incontinence and evacuatory disorders associated with the ileoanal pouch can be particularly problematic and difficult to treat using conventional therapies. Biofeedback therapy is a behavioural treatment which is non-invasive and offers a non-surgical approach as an alternative or adjunct for patients with functional bowel disorders. The theoretical basis for biofeedback is 'learning through reinforcement' or 'operant conditioning'. Methods: This was a retrospective single centre study. All patients attending for biofeedback at our institution between Jan 2012 and Oct 2017 were identified to include all those that attended for a pouch related problems. We recorded patient reported subjective improvements following biofeedback. The validated International Consultation on Incontinence Questionnaire was used to assess improvement in incontinent symptoms, and the evacuatory disorder questionnaire was used to assess improvement in evacuatory disorders. Results: n=26. Based on patients' feedback at next clinical encounter following biofeedback, nine reported much improvement, 11 reported some improvement and six reported no improvement. In the group treated for incontinence, quality of life improved significantly from a median pre-treatment score of 80 to a post-treatment score of 41 (p=0.01) (table 1). Biofeedback reduced pain, bloating, straining and laxative use in patients with evacuatory disorders. Conclusions: Biofeedback is associated with significant improvement in the quality of life as well as possible improvements in symptoms related to both incontinence and evacuatory disorders. It is probably an underused service. Further larger prospective studies are required to assess the efficacy of biofeedback in pouch related dysfunction.